An investigation of factors that influence the duration of IT outsourcing relationships - Goo, Jahyun; Kishore, Rajiv; Nam, Kichan; Rao, H. Raghav; Song, Yongil (ELSEVIER, 2007)
Past studies in the IT outsourcing area have examined the management of IT outsourcing relationships from a variety of perspectives. The present paper extends this line of research. In this study, we take a multi-theoretic perspective to explore factors that determine the duration of continuing IT outsourcing relationships between vendor and client firms. Five ex-ante and two expost factors that may influence relationship duration were examined in this study. Data for this study were collected using a nationwide survey. To investigate the dynamics of continuing outsourcing relationships through repetitive contracts, we performed survival analysis using an accelerated failure-time (AFT) model. Four factors are found to have a significant relationship with relationship duration as hypothesized. However, three factors, of which two are ex-post factors, are found to not have a significant impact on outsourcing relationship duration. Implications and contributions of the study are discussed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: EMPIRICAL-EVIDENCE; INFORMATION; INVESTMENTS; PERSPECTIVE; INNOVATION; DIFFUSION; ASSIMILATION; PERFORMANCE; GOVERNANCE; SUPPLIERS